Establishment of a Method for Measuring Antioxidant Capacity in Urine, Based on Oxidation Reduction Potential and Redox Couple I2/KI - Tinghui Cao; Min He; Tianyu Bai; Hui Liu (Bioinorganic Chemistry and Applications)
Objectives. To establish a new method for determination of antioxidant capacity of human urine based on the redox couple I2/KI and to evaluate the redox status of healthy and diseased individuals. Methods. The method was based on the linear relationship between oxidation reduction potential (ORP) and logarithm of concentration ratio of I2/KI. ORP of a solution with a known concentration ratio of I2/KI will change when reacted with urine. To determine the accuracy of the method, both vitamin C and urine were reacted separately with I2/KI solution. The new method was compared with the traditional method of iodine titration and then used to measure the antioxidant capacity of urine samples from 30 diabetic patients and 30 healthy subjects. Results. A linear relationship was found between logarithm of concentration ratio of I2/KI and ORP (R2=0.998). Both vitamin C and urine concentration showed a linear relationship with ORP (R2=0.994 and 0.986, resp.). The precision of the method was in the acceptable range and results of two methods had a linear correlation (R2=0.987). Differences in ORP values between diabetic group and control group were statistically significant (P<0.05). Conclusions. A new method for measuring the antioxidant capacity of clinical urine has been established.